Exploring student perceptions of the Osmosis digital learning platform in undergraduate medical education and its influences on motivation and inclusivity - Sanat Kulkarni; Erin Lawson-Smith; Laura Mongan; Rachel Westacott; Dawn Jackson (BMC Medical Education)
Abstract Background The increasing incorporation of digital learning platforms has transformed pedagogical approaches in medical education. However, these tools are under-researched and under-theorised. In the 2022/23 academic year, an asynchronous, personalised digital learning tool (Osmosis) was provided to all medical students at one of the largest medical schools in the United Kingdom. We explored students’ experience of digital learning platforms, including Osmosis, and their influences on student motivation and inclusion. Methods We conducted a qualitative study of second to final year medical students at the University of Birmingham. Data were collected through 10 semi-structured interviews and one focus group. The fifteen participants were purposively sampled based on year group, gender, ethnicity, international student status, self-reported health challenges, caring responsibilities and financial difficulties. Interviews were audio-recorded, transcribed and thematically analysed using the Framework Method. Data were analysed through the lens of self-determination theory (SDT) which focuses on the psychological needs of autonomy, self-efficacy and interconnectedness for achieving intrinsic motivation. Results Five overarching themes were identified in relation to digital learning tools: (1) navigating complexity within the digital learning environment, (2) benefits and pitfalls of autonomous digital learning, (3) efficiency and depth in learning and promoting self-confidence, (4) social influences on digital learning and (5) curriculum level considerations. Aligned to SDT, digital tools promoted students’ autonomy, self-efficacy and relatedness thereby facilitating intrinsic motivation. Online tools, including the Osmosis platform, supported student inclusivity and accessibility, helping students overcome health and learning challenges. However, lack of formal guidance towards online platforms, misalignment to the local curriculum and concerns over reliability were key barriers to their use. Conclusion Digital learning tools play an increasingly important role within modern medical education, positively impacting student motivation and inclusion. Nevertheless, greater focus must be placed on providing local guidance in accessing such tools, alongside constructively aligning their integration with other elements of the curriculum. Retaining medical students is vital to the future of patient care and it is ever more critical that higher education institutions prioritise student motivation, inclusion and wellbeing. Optimising integration of digital learning platforms therefore may be one means of achieving this. Clinical trial number Not applicable.